Coupling of electric field and bending modulated ballistic transport properties of copper nanowires. (March 2015) - He, C.; Huang, R. Y.; Shi, Z. Q.; Zhang, W. X.
Abstract : Coupling effect of electric field and bending on ballistic transport properties of copper nanowires (NWs) has been studied for the future application in solar cells and flexible displays. Our density function calculations show that when electric field strength V is equal to 0·5 V Å −1, both structures (non-helical strand and helical strand) of CuNW are more stable and exhibit excellent quantum conductivity. Moreover, the helical structures have better stability than the non-helical ones since it owns higher collapse resistant f when V = 1 V Å −1 . These results suggested that coupling of electric field and bending can be used to tune transport properties of CuNWs, which may be of help in the design of flexible nanodevices.